Emotional and Behavioural Problems Among Refugee Children and Adolescents Living in South Australia. (19th October 2011) - Ziaian, Tahereh; de Anstiss, Helena; Antoniou, Georgia; Baghurst, Peter; Sawyer, Michael
<x xml:space="preserve">Abstract</x> While there is a growing body of literature on the mental health status of adult refugees, children have been relatively neglected in research, particularly in Australia. This study investigated the prevalence of emotional and behavioural problems and patterns of service utilisation among 530 refugee children and adolescents aged 4–17 years living in South Australia. Parents and teachers of children aged 4–17 years and adolescents aged 13–17 years completed the appropriate versions of the Strengths and Difficulties Questionnaire. Of the 11.0% of children and adolescents found to have borderline or abnormal emotional and behavioural problems, only 13.0% accessed professional help. The study has practical implications for policy and practice.